DECENNIAL: A Creative Legacy | 10 year anniversary, Art Seen Gallery, Nicosia, group exhibition, curated by Maria Stathi, Founder & Director, Art Seen - Pericleous, Vicky (My University, 2025)
Art Seen Celebrates a Decade of Creativity with the Exhibition “DECENNIAL: A Creative Legacy” Art Seen, one of Cyprus’ leading contemporary art galleries and cultural organizations, is proud to present DECENNIAL: A Creative Legacy, an exhibition marking the gallery’s 10th anniversary. The show will open on October 9 in Nicosia and run until November 7, featuring new works by a dynamic group of artists who have held solo exhibitions at Art Seen and who have played a vital role in shaping its remarkable journey. The exhibition adopts an archival approach in both curatorial concept and installation, reflecting on all the solo shows that have taken place at the gallery over the past decade. It highlights the participating artists, their practices, and the trajectories of their work, while reaffirming Art Seen’s role as an open space for dialogue, experimentation, and research — a platform fostering creativity and collaboration. In parallel, a series of events will accompany the exhibition, including curatorial workshops, educational programs, and the launch of a special anniversary publication. Participating artists: Chris Akordalitis, Spyros Anastasiou, Vasia Adamou Vanezi, Clare Burnett, Marina Genadieva, Gary Colclough, Panayiotis Doukanaris, Kyriacos Kallis, Eleni Kamma, Vicky Pericleous, Amy Stephens, Diana Taylor, Amikam Toren, Alison Turnbull, Nicos Philippou & Marilena Zackheos . The artists will present a wide range of practices — drawing, painting, collage, sculpture, video, and installations — spread throughout the gallery space. From smaller works conceived as intimate gestures to large-scale installations, each artist brings a distinct visual language, employing different mediums to explore diverse approaches and representations. Over the past ten years, Art Seen has established itself as a cultural beacon in Nicosia, hosting more than 35 significant exhibitions and collaborating with over 100 talented artists from Cyprus and abroad. Since its founding in 2015, the gallery has been at the forefront of the Cypriot art scene, introducing innovative curatorial practices and supporting the creative development of both emerging and established artists. “Ten years ago, we set out to create a space where art could inspire, challenge, and bring communities together, contributing to the island’s cultural heritage. Today, we celebrate not only our own journey, but also the artists, audiences, and supporters who have made Art Seen what it is today.” The exhibition is funded by the Deputy Ministry of Culture.
Keywords: Arts; Contemporary Art Practices; Artist-led Research and Experimentation; Curatorial Practices; Art Catalogues; Art Puplications; Artist's Solo Shows